ANALISIS MEMPREDIKSI FINANCIAL DISTRESS DAN FAKTOR PENGARUHNYA PADA PERUSAHAAN PERTAMBANGAN BEI TAHUN 2019 – 2021 - Juan Carlos Pangestu; Denise Insan Hirliana (Owner : Riset dan Jurnal Akuntansi, 2023)
Financial distress conditions can occur in a company and this will disrupt the continuity of the company's operations so it is important to know what causes the possibility of a financial distress condition. This study aims to examine the influence of Debt To Total Assets, Audit Committee, ROA, Current Ratio, Company Size. on Financial Distress predictions for mining sector companies listed on the Indonesia Stock Exchange in 2019-2021. Sampling was done by purposive sampling technique. This type of research uses descriptive statistical tests and logistic regression methods. The objects in this study are the financial reports of mining sector companies listed on the IDX from the 2019 -2021 period. The results showed that all independent variables had no effect on financial distress. The research model has a predictive accuracy of financial distress of 84.2 percent. Future research should use non-financial factors or change the research model to be qualitative